Comparison of Mean Dimensional Changes in Acrylic Resin Specimen Disinfected with Wet Versus Dry Microwave Cycles at Different Time Intervals - Malik, Faizan; Nasir Shah, Syed; Ali Chughtai, Mohammad; Khan, Ehtesham; Khalid, Mariya; Mian, Hamad Ishtiaq (Journal of Postgraduate Medical Institute, 2025)
Objective: To determine the mean dimensional changes in acrylic resin specimens disinfected with wet and dry microwave cycles for disinfection. Methodology: Acrylic resin specimens were fabricated using a stainless-steel mold measuring 64 x 10 x 3.3 mm in length, width, and thickness, respectively, according to ISO1567 standards. The acrylic resin specimens were measured using digital Vernier calipers and was then divided into ten groups through lottery method. After completing microwave irradiation cycles, measurements of each specimen were recorded using digital Vernier caliper and compared with the readings recorded before microwave treatment, post-irradiation dimensions of acrylic resin specimens were documented on predesigned performa. Results: All acrylic resin specimens exhibited approximately no dimensional changes in all recorded measurements after microwave irradiation cycles. The results were statistically non-significant, with all t-tests having values of p>0.05 for each measured distance between the points. No deformations were seen in all groups’ specimens except the greatest deformation, which was found in the specimens of group F; that also showed a little change in length. Conclusion: It may be concluded that these tested acrylic resin specimens demonstrated no deformation under experimental conditions at 850 W of dry and wet microwave irradiations for 3, 6, 9, 12, and 15 minutes and can be considered a suitable method for acrylic denture disinfection.